Campo Laborde: A Late Pleistocene giant ground sloth kill and butchering site in the Pampas - Politis, Gustavo Gabriel (2019)
The extinction of Pleistocene megafauna and the role played by humans have been subjects of constant debate in American archeology. Previous evidence from the Pampas region of Argentina suggested that this environment might have provided a refugium for the Holocene survival of several megamammals. However, recent excavations and more advanced accelerator mass spectrometry radiocarbon dating at Campo Laborde site in the Argentinian Pampas challenge the Holocene survival of Pleistocene megamammals and provide original and high-quality information documenting direct human impact on the Pleistocene fauna. The new data offer definitive evidence for hunting and butchering of Megatherium americanum (giant ground sloth) at 12,600 cal years BP and dispute previous interpretations that Pleistocene megamammals survived into the Holocene in the Pampas.